2008
DOI: 10.1186/1746-1596-3-s1-s19
|View full text |Cite
|
Sign up to set email alerts
|

Portable telepathology: methods and tools

Abstract: Telepathology is becoming easier to implement in most pathology departments. In fact e-mail image transmit can be done from almost any pathologist as a simplistic telepathology system. We tried to develop a way to improve capabilities of communication among pathologists with the idea that the system should be affordable for everybody. We took the premise that any pathology department would have microscopes and computers with Internet connection, and selected a few elements to convert them into a telepathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
1
8
0
1
Order By: Relevance
“…), physical and economical constraints in the access to broad band data-transmission network, represent a major obstacle to the transmission of images for the purpose of tele-pathology in most remote and disadvantaged areas of the world. These limitations and the deriving challenges were recently extensively reviewed by Alfaro and Roca, who defined the minimum requirements for a system of image transmission,[ 3 ] however without mentioning MMS as an alternative to the internet for transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), physical and economical constraints in the access to broad band data-transmission network, represent a major obstacle to the transmission of images for the purpose of tele-pathology in most remote and disadvantaged areas of the world. These limitations and the deriving challenges were recently extensively reviewed by Alfaro and Roca, who defined the minimum requirements for a system of image transmission,[ 3 ] however without mentioning MMS as an alternative to the internet for transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, complexity and costs of equipment, as well as physical and economical constraints in the access to broad band data-transmission network, still represent a considerable obstacle to the transmission of images for the purpose of tele-pathology. Even most recent extensive reviews of these limitations and the deriving challenges,[ 3 ] do not consider the possibility of capturing high quality images directly from the microscope, and transmitting them for distance diagnosis purposes using a mobile cell-phone (m-phone), without the need of any adaptor or additional technology. Based on the results of our testing, experience, and investigation on accessibility, we argue that the simple procedure we propose represents a far more appropriate and promising approach compared with those previously described.…”
Section: Introductionmentioning
confidence: 99%
“…Streaming video approaches are ubiquitous in health care industry, news organizations, commercial interests and some government sites and are proven valuable adjuncts to biomedical education. Streaming within a secure environment as described by Jeun and colleagues, 35 for multicenter radiology communications is more complex than open web streaming 37,38 by oncologists at secure sites. Streaming video has been reported in many applications; Garrison 39 has suggested it is moving into the mainstream.…”
Section: Video Streamingmentioning
confidence: 99%
“…All that is required to implement this system is a camera, a universal microscope adapter for the camera, a device to connect the camera to the computer, and software for the remote image transfer. 17,60 Another important challenge that is usually overseen is the attitude of practicing pathologists toward this change. Generally speaking, a good percentage of anatomical pathologists are not in favor of the transition into digital practice.…”
Section: Challenges For Pathology Informaticsmentioning
confidence: 99%
“…As any pathology department will have microscopes and computers with Internet connection, with a few added elements (such as a camera connected to the microscope and software for remote image transmission), a telepathology station can be constructed. 17 The Internet serves as a repository of information and transmission of images and is one of the easiest infrastructures to use in this aspect to allow global consultation. 18 Different types of telepathology communications are available for diagnostic and consultation services, which were reviewed in detail in the study by Cross 19 As shown in Table 2, static image telepathology is the simple form of telepathology communication, which functions by capturing selected digital images at one site and thereafter by transmitting them electronically in the form of email attachments to the remote site.…”
Section: Telepathology: Applications and Limitationsmentioning
confidence: 99%